2005
DOI: 10.1016/j.femsle.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ferrichrome A biosynthetic gene cluster in the homobasidiomyceteOmphalotus olearius

Abstract: Under iron deprivation Omphalotus olearius was found to produce the hydroxamate siderophore ferrichrome A. A gene cluster consisting of three genes: fso1, a nonribosomal peptide synthetase whose expression is enhanced in the absence of iron; omo1, a l-ornithine-N(5)-monooxygenase; and ato1, an acyltransferase probably involved in the transfer of the methylglutaconyl residue to N(5)-hydroxyorinithine was identified. The fso1 sequence is interrupted by 48 introns and its derived protein sequence has a similar st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Supporting this hypothesis, C. heterostrophus, A. brassicicola, and F. graminearum NPS6 genes were upregulated under iron-depleted conditions ( Figure 4) as reported previously for genes involved in siderophore biosynthesis in other fungi (Yuan et al, 2001;Yamada et al, 2003;Welzel et al, 2005). HPLC analyses of C. heterostrophus broth and mycelial fractions from wild-type and Dnps6 strains indicated that NPS6 is indeed involved in siderophore biosynthesis, specifically in extracellular siderophore biosynthesis.…”
Section: Nps6 Encodes An Nrps Involved In Extracellular Siderophore Bsupporting
confidence: 86%
“…Supporting this hypothesis, C. heterostrophus, A. brassicicola, and F. graminearum NPS6 genes were upregulated under iron-depleted conditions ( Figure 4) as reported previously for genes involved in siderophore biosynthesis in other fungi (Yuan et al, 2001;Yamada et al, 2003;Welzel et al, 2005). HPLC analyses of C. heterostrophus broth and mycelial fractions from wild-type and Dnps6 strains indicated that NPS6 is indeed involved in siderophore biosynthesis, specifically in extracellular siderophore biosynthesis.…”
Section: Nps6 Encodes An Nrps Involved In Extracellular Siderophore Bsupporting
confidence: 86%
“…We presume fer3 to encode the peptide synthetase catalyzing ferrichrome A biosynthesis. In the gene cluster on chromosome 2, we also found an acylase gene, fer5, that displays similarity to an acyltransferase found in the putative ferrichrome A biosynthetic gene cluster of Omphalotus olearius (Welzel et al, 2005) (Table 1). Fer5 could potentially carry out acylation of N 5 -hydroxy-L-Orn residues in ferrichrome A.…”
Section: Identification Of Coregulated Gene Clusters Involved In Ironmentioning
confidence: 71%
“…Because the genes of a particular secondary metabolite biosynthetic pathway tend to be clustered in fungi, clustering of AbPOPA or AbPOPB with other genes involved in amatoxin biosynthesis would suggest a role for one or both of these genes in amatoxin biosynthesis (1,27,35). To test this, we screened a lambda phage clone library with AbPOPA and AbPOPB, and two hybridizing clones were sequenced completely.…”
Section: Resultsmentioning
confidence: 99%
“…Clustering of genes involved in a common pathway is the usual situation in fungal secondary metabolism (32). Although there has been less work done on the genetics of secondary metabolism in basidiomycetes than on that in ascomycetes, this appears to be the emerging consensus for this group of organisms as well (1,27,35).…”
Section: Discussionmentioning
confidence: 99%